Common currency and intra-regional trade in the Central African Monetary Community (CEMAC) - Divine Ngenyeh Kangami; Oluyele F. Akinkugbe (Journal of African Trade, 2021)
We applied the threshold autoregressive and difference-in-differences techniques to examine the effects of adopting a common currency on bilateral trade flows between member states of the Central African Economic and Monetary Community (CEMAC) customs union, over the period from 1980 to 2013. We found evidence of a sample split-a probable indication of the presence of a single threshold corresponding to the year 1994 when the Coopération financière en Afrique centrale (CFA) franc, a common currency, was introduced in CEMAC. Our results also show that the adoption of the CFA franc did not contribute to growth in CEMAC intra-regional trade. The results are robust in that they take into account country fixed effects and suggest a turning point after 1994, between the common currency and the flow of intra-regional trade. More generally, our results provide evidence against the claim that a common currency leads to increased intra-regional trade.
Keywords: 330; CEMAC; CFA franc; common currency; difference in differences; exchange rate; intra-regional trade; real effective exchange rate; threshold autoregression; WAEMU